THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT - Putri Esti Cahyani; Siswanto Siswanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
Leadership and employee engagement are essential factors in the effectiveness of employee performance in the company. Those two indicators cannot be separated from the sustainability of an organization or company. The purpose of this study is to analyze the direct and indirect effects of transformational leadership on employee performance and how much employee engagement mediates the effect of transformational leadership on employee performance. This research utilized an explanatory quantitative approach and used 101 respondents as the sample. The data was collected by using questionnaires and analyzed using the Partial Least Square (PLS) analysis tool. The results of the testing show that there is a significant influence between transformational leadership on the performance of employees of PT. Victory International Futures Malang. While the employee engagement variable mediates the influence of transformational leadership on the performance of employees of PT.Victory International Futures Malang.Keywords : Transformational leadership, Employee performance, Employee engagement, Explanatory quantitative approach